Short-Term Effects of Deliberate Subparaneural or Subepineural Injections With Saline Solution or Bupivacaine 0.75% in the Sciatic Nerve of Rabbits - Laredo, Francisco G.; Belda, Eliseo; Soler, Marta; Gil, Francisco; Murciano, José; Sánchez-Campillo, Joaquín; Agut, Amalia (Frontiers in Veterinary Science, 2020)
Background: Ultrasound (US)-guided techniques for peripheral nerve blockade have revealed that intraneural injections are relatively frequent and not necessarily associated with neurological deficits. Objectives: To evaluate the short-term effects of deliberate injections performed under direct vision in two different sites of the sciatic nerve (ScN). Material and Methods: Seventy-two New Zealand white rabbits randomly assigned to one of four experimental groups (n = 18) were employed. All procedures were conducted at a proximal femoral level where the ScN incorporates the common peroneal nerve and the tibial nerve (TN). Fixed volumes of 0.5 ml of saline solution (ES group) or bupivacaine 0.75% (EB group) were administered extrafascicularly inside the paraneurium of the ScN or intrafascicularly (IS and IB groups) under the epineurium of the TN. Cross-sectional area (CSA) and relative echogenicity (RE) of the entire ScN were determined by US before injections, after injections, and at 3 and 7 days. ScN samples were obtained for structural and ultrastructural histopathological studies. Proprioceptive, sensorial, and motor function were clinically evaluated on a daily basis. Results: The CSA of the ScN increased significantly immediately after injections when compared with pre-injection values in all groups (p < 0.05). The RE of the ScN decreased in relation to pre-injection values in all groups (p < 0.05). The CSA and RE of the ScN returned to normal values 7 days after injections in almost all groups. Injected nerves showed histological signs of mild perineural inflammation. Histopathological scores were not significantly different between groups (p > 0.05). The architecture of the ScN was preserved in all rabbits at 3 days and in 31/32 rabbits at 7 days. A focal area of damaged nerve fibers with degeneration of the axons and myelin sheath affecting the TN was observed in one rabbit of the IB group. Nerve function was not clinically impaired in any case. Conclusion: Despite the lack of severe nerve disruption observed in most rabbits, the evidence of a focal area of damaged nerve fibers in one rabbit injected intrafascicularly with bupivacaine confirms that intrafascicular injections should be avoided as they may increase the risk of nerve damage.